Pengembangan Media Pembelajaran Roda Pintar pada Subtema Perubahan Wujud Benda Kelas III UPT SD Negeri 98 Gresik - Tika Laurina; Iqnatia Alfiansyah (Journal on Education, 2023)
This development research aims to develop smart wheel learning media on the sub-theme of changes in the shape of objects that are suitable for learning. In this study, the ADDIE development model was implemented through 5 stages including Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study were 18 students in class III UPT SD Negeri 98 Gresik. The techniques used for data collection were media expert validation questionnaires, material expert validation questionnaires, and student response questionnaires. The results of the validation of media experts obtained 94.95% and material experts reached 93.25%, both of which indicated the "valid" category. Smart wheel media is also very effective for use as a learning medium in class III UPT SD Negeri 98 Gresik, by obtaining an average student response of 95.6% in the "very effective" category. So it can be concluded that the smart wheel learning media on the sub-theme of changing the shape of objects meets valid criteria and is very effectively used in the learning process.